Examining Readiness of E-Learning Implementation Using Aydin and Tasci Model: A Rural University Case Study in Indonesia - Esa, Firmansyah; Muhammad Agreindra, Helmiawan; Ali, Rahman; Maya, Suhayati; Aedah, Abd Rahman (2021)
Humankind throughout the world are currently in a state of collapse due to the outbreak of Corona Virus Disease (COVID-19) which began in Wuhan, China. Later on, it was announced as the pandemic situation according to WHO. Overall countries have implemented social distancing, while Indonesia has implemented a policy of learning from home, working from home, and worship at home or better known as work from home (WFH). This study aimed to determine the level of readiness to implement e-learning during WFH due to the pandemic COVID-19 spreads along with the challenges in the 4.0 revolution in millennials. The model that used was the Aydin & Tasci model which measures four main factors namely technology, innovation, people, and self-development. Data collection was conducted online using Google Form, while data processing uses a descriptive statistical method mapped based on the Aydin & Tasci version of the e-learning readiness index. The results showed that the overall e-learning readiness index might indicate that the system was ready to be implemented, but required a slight increase in several factors, namely innovation increase, human, and self-development factors. The results and discussion of the study showed the readiness of e-learning to follow the demands of Revolution 4.0, even though it was done during WFH because of the COVID-19 pandemic outbreak.